Reduzierte Thrombozytenaggregation bei einem Jungen mit Skorbut - Dey, F.; Möller, A.; Kemkes-Matthes, B.; Wilbrand, J.-F.; Krombach, G. A.; Neubauer, B.; Hahn, A. (Klinische Pädiatrie, 2012)
Pediatric scurvy is a rare condition characterized by perifollicular petechiae and bruising, hemorrhagic gingivitis and musculoskeletal symptoms, all assumed to be predominantly related to abnormal collagen structure. We report on a 9-year-old autistic boy with vitamin C deficiency due to a highly limited food range presenting with multiple petechiae, gum bleeding and debilitating bone pain, in whom platelet aggregometry revealed a distinctly reduced thrombocyte aggregation, normalizing after vitamin C supplementation. This observation indicates that platelet dysfunction may additionally contribute to the hemorrhagic diathesis in scurvy, and demonstrates that ascorbic acid deficiency should be considered in children with an otherwise unexplained acquired thrombocytopathy
Keywords: Scurvy; thrombocytopathy; thrombocyte aggregometry; vitamin C deficiency; childhood